Hepatoprotective effect of curcumin and alpha-tocopherol against cisplatin-induced oxidative stress - Sarawoot Palipoch (2018)
Background:cis-Diammineplatinum (II) dichloride (cisplatin) is the important anti-cancer agent useful in treatment of various cancers. Unfortunately, it can produce unwanted side effects in various tissues, including the liver. The present study investigated the possible protective role of curcumin and α-tocopherol against oxidative stress-induced hepatotoxicity in rats upon cisplatin treatment.Methods: Male Wistar rats were divided into five groups (n = 5). Saline and Cis groups, rats were intraperitoneal (i.p.) injected with normal saline and cisplatin [20 mg/kg body weight (b.w.)], respectively. Cis + α-tocopherol group, Cis + Cur group and Cis + α-tocopherol + Cur group, rats were pre-treated with a single dose of α-tocopherol (250 mg/kg b.w.), curcumin (200 mg/kg b.w.) and combined α-tocopherol with curcumin, respectively, for 24 h prior the administration of cisplatin. After 72 h of first injection, specimens were collected. Liver enzyme, lipid peroxidation biomarker, liver histopathology and gene expression of liver nicotinamide adenine dinucleotide phosphate (NADPH) oxidase were investigated.Results: Cisplatin revealed a significant increase of hepatic malondialdehyde (MDA) levels and a significant reduction of hepatic superoxide dismutase (SOD) and catalase activities compared to the saline group. It elicited a marked increase of the serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels and demonstrated the liver pathologies including liver congestion, disorganization of hepatic cords and ground glass appearance of hepatocytes. It also demonstrated a significant increase of NADPH oxidase gene expression compared to saline group. Pre-treatment with combined curcumin and α-tocopherol improved the liver enzymes, lipid peroxidation biomarker, liver histopathology and gene expression of liver NADPH oxidase in cisplatin-treated rats.Conclusions: The findings indicate that pre-treatment with combined curcumin and α-tocopherol can protect cisplatin-induced hepatotoxicity including the biochemical, histological and molecular aspects. The down-regulations of NADPH oxidase gene expression may be involved in abrogating oxidative stress via reduction of reactive oxygen species (ROS) production. © 2014 Palipoch et al.; licensee BioMed Central Ltd.